THE EFFECT OF FINANCIAL LITERACY AND FINANCIAL ATTITUDES ON THE FINANCIAL PERFORMANCE - Rosyida, Riska Ainur; Wicaksono, Achmad (COMPETITIVE, 2025)
This study investigates the financial performance of MSMEs in the beverage sector in Tulangan sub-district, Sidoarjo district, in relation to their financial attitudes and literacy. Strong financial literacy enables businesses to plan for the future, manage cash flow, and control costs, while positive financial attitudes foster disciplined income and expense management, thereby enhancing profitability and business sustainability. The study used a quantitative approach to survey 77 MSMEs players using a Likert scale questionnaire, and it used validity, reliability, normality, heteroscedasticity, multicollinearity, T-test, and F-test to analyze the data. The findings show that financial attitudes and literacy have a significant impact on beverage MSMEs' financial success. Financial attitudes serve as a foundation for sound decision-making, while financial literacy enhances financial management capabilities. This research contributes theoretically by empirically demonstrating that these two factors are crucial for the growth and stability of small businesses. However, since the study focuses solely on the beverage industry in one region, its findings may not be generalizable to other sectors; future research could incorporate additional variables such as financial technology or government policies for a more comprehensive analysis.